Metodología para la identificación, análisis y retroalimentación de causas vitales que originan el ausentismo en la gerencia comercial de la empresa Triple A S.A. E.S.P. para la toma de acciones en pro del mejoramiento continuo de los procesos. (2010)
This project describes a complete work of design and implementation of a device capable of automatically controlling the supply of oxygen medical of hospital patients; project presented a 6 months development onsite at the CLINICA LA MERCED I.P.S. at Barranquilla city. The study focused on the supply of oxygen for nasal cannula, because this is one of the procedures of oxygen therapy most widespread throughout the hospital, taking into account the respiratory Physiology and Anatomy of the respiratory system human. System of automatic control for the supply of oxygen in humans, this enhanced by a microcontroller responsible for all actions of the device, in this case the PIC 16f873 programmed in C language and compiled from CCS - C specialized software. Implemented a stage display and an effectors in charge of a valve that regulates the flow rat of the oxygen supplied. On the other hand electronic development was assisted by design and simulation programs grouped in Proteus.